Opportunities and Challenges in Digital Transformation of Education - Qu, Liaojian (Science Insights Education Frontiers, 2024)
The World is facing a fast and radical change due to the expedited development of digital technologies. Advances in digital technology are constantly driving the digital transformation of society as a whole. The concept of “digital transformation” first emerged in 1968 and became distinctive in the research literature after the year of 2014 (Reis et al, 2018). In its broad sense, digital transformation refers to the process that new digital technologies are integrated into all sectors of human activity, fundamentally changing all aspects of human life. This leads to a world that is increasingly experienced with, through, and by information technology (Stolterman & Fors, 2004).